177Lu‐PSMA radioligand therapy effectiveness in metastatic castration‐resistant prostate cancer: An updated systematic review and meta‐analysis. Issue 7 (14th March 2022) - Sadaghiani, Mohammad S.; Sheikhbahaei, Sara; Werner, Rudolf A.; Pienta, Kenneth J.; Pomper, Martin G.; Gorin, Michael A.; Solnes, Lilja B.; Rowe, Steven P.
Abstract: Background: An updated systematic review and meta‐analysis of relevant studies to evaluate the effectiveness of prostate‐specific membrane antigen (PSMA)‐targeted endoradiotherapy/radioligand therapy (PRLT) in castration resistant prostate cancer (CRPC). Methods: A systematic search was performed in July 2020 using PubMed/Medline database to update our prior systematic review. The search was limited to papers published from 2019 to June 2020. A total of 472 papers were reviewed. The studied parameters included pooled proportion of patients showing any or ≥50% prostate‐specific antigen (PSA) decline after PRLT. Survival effects of PRLT were assessed based on pooled hazard ratios (HRs) of the overall survival (OS) according to any PSA as well as ≥50% PSA decline after PRLT. Response to therapy based on ≥50% PSA decrease after PRLT versus controls was evaluated using Mantel‐Haenszel random effect meta‐analysis. All p values < 0.05 were considered as statistically significant. Results: A total of 45 publications were added to the prior 24 studies. 69 papers with total of 4157 patients were included for meta‐analysis. Meta‐analysis of the two recent randomized controlled trials showed that patients treated with 177 Lu‐PSMA 617 had a significantly higher response to therapy compared to controls based on ≥50% PSA decrease. Meta‐analysis of the HRs of OS according to any PSA decline and ≥50% PSA decline showed survival prolongation after PRLT. Conclusions: PRLT results in higher proportion of patients responding to therapy based on ≥50% PSA decline compared to controls. Any PSA decline and ≥50% PSA decline showed survival prolongation after PRLT. Advances in knowledge: This is the first meta‐analysis to aggregate the recent randomized controlled trials of PRLT which shows CRPC patients had a higher response to therapy after PRLT compared to controls.